Strategi Pemasaran Jasa Pendidikan Anak Usia Dini Untuk Membangun Kepercayaan Target Pasar - Kartika Sari Yudaninggar (Universitas Pamulang, 2022)
The pandemic has indeed changed almost all aspects of life and activities in society. Early childhood is one of the groups experiencing the impact of these changes. One of them is the inhibition of the learning process in early childhood. On the other hand, parents are also busy and often run out of ideas to play with their children. Seeing this opportunity, Kelas Main Harmoni offers a children's play class program online via a zoom meeting. Uniquely, Kelas Main Harmoni is still new, and is not a formal educational institution, but Kelas Main Harmoni can build the trust of parents to register their children and play together in Kelas Main Harmoni program. This study used descriptive qualitative method. This study involved informants who are founders, as well as parents of Kelas Main Harmoni participants to conduct interviews to find out the marketing strategy carried out by Kelas Main Harmoni. The results of this study indicate that the strategy taken to build the trust of parents is to continue to develop and focus on aspects of the product in the form of services, as well as people, or the quality of teachers in Kelas Main Harmoni.